Centromere-Specific Retrotransposons and Very-Long-Chain Fatty Acid Biosynthesis in the Genome of Yellowhorn (Xanthoceras sorbifolium, Sapindaceae), an Oil-Producing Tree With Significant Drought Resistance - Liu, Hui; Yan, Xue-Mei; Wang, Xin-rui; Zhang, Dong-Xu; Zhou, Qingyuan; Shi, Tian-Le; Jia, Kai-Hua; Tian, Xue-Chan; Zhou, Shan-Shan; Zhang, Ren-Gang; Yun, Quan-Zheng; Wang, Qing; et al. (Frontiers in Plant Science, 2021)
In-depth genome characterization is still lacing for most of biofuel crops, especially for centromeres which play a fundamental role during nuclear division and in the maintenance of genome stability. This study applied long-read sequencing technologies to assemble a highly contiguous genome for yellowhorn (Xanthoceras sorbifolium), an oil-producing tree, and conducted extensive comparative analyses to understand centromere structure and evolution, and fatty acid biosynthesis. We produced a reference level genome of yellowhorn, ~470 Mb in length with ~95% of contigs anchored onto 15 chromosomes. Genome annotation identified 22,049 protein-coding genes and 65.7% of the genome sequence as repetitive elements. We identified the centromeric regions on each chromosome and found enrichment of centromere-specific retrotransposons of LINE1 and Gypsy in these regions which evolved recently (~0.7 MYA). We compared the genomes of three cultivars and found frequent inversions. We analyzed the transcriptomes from different tissues and identified the candidate genes involved in very-long-chain fatty acid biosynthesis and their expression profiles. Collinear block analysis showed that yellowhorn shared the gamma (γ) hexaploidy event with Vitis vinifera but did not undergo any further whole-genome duplication. This study provides excellent genomic resources for understanding centromere structure and evolution, and for functional studies in this important oil-producing plant.